Mobile-based Nahwu Sharaf Learning Application: Aplikasi Pembelajaran Nahwu Sharaf berbasis Mobile - Sumarno; Hindarto; Khoiri; Efendy, Egha Arya; Agung, Aprelareza (Universitas Muhammadiyah Sidoarjo, 2024)
The development of information and communication technology has brought significant changes in various aspects of life, including in the field of education. One of the main challenges in learning Arabic is mastering Nahwu and Sharaf, which are important branches of Arabic grammar. This study aims to develop a mobile application specifically designed to facilitate learning Nahwu and Sharaf for the general public. This application was developed using the Research and Development (R&D) method which includes the stages of needs analysis, design, development, testing, and evaluation. The main features of the application include learning materials to measure user understanding. In addition, this application is equipped with learning reminder features and progress tracking to assist users in the independent learning process. The trial results show that this application is effective in improving a person's understanding and skills in Nahwu and Sharaf. This application also received a positive response from users who felt that the learning methods presented were more interesting and interactive than conventional methods. Thus, it is hoped that this application can be an effective alternative solution in learning Nahwu and Sharaf, and can be widely applied in various institutions.